Mast Cells in Peritoneal Fluid From Women With Endometriosis and Their Possible Role in Modulating Sperm Function - Borelli, Violetta; Martinelli, Monica; Luppi, Stefania; Vita, Francesca; Romano, Federico; Fanfani, Francesco; Trevisan, Elisa; Celsi, Fulvio; Zabucchi, Giuliano; Zanconati, Fabrizio; Bottin, Cristina; Ricci, Giuseppe (Frontiers in Physiology, 2020)
Endometriosis is a local pelvic inflammatory process, frequently associated with infertility, with altered function of immune-related cells in the peritoneal environment. Mast cells are known to be key players of the immune system and have been recently involved in endometriosis and in infertility, with their mediators directly suppressing sperm motility. In this study, we evaluated the mast cell population and their mediators in the peritoneal fluid of infertile patients with endometriosis and their impact on human sperm motility. Peritoneal fluids, collected by laparoscopy from 11 infertile patients with endometriosis and 9 fertile controls were evaluated for the presence of mast cells, tryptase levels and their effect on sperm motility. Furthermore, an in vitro model of mast cells-sperm interaction in peritoneal fluid was set up, using LAD2 cell line as a mast cell model, and analyzed from a functional as well as a morphological point of view. Mast cell peritoneal fluid population and its main mediator, tryptase, is more represented in endometriosis confirming an involvement of these cells in this disease. Anyway it appears unlikely that tryptase enriched peritoneal fluid, which fails to inhibit sperm motility, could contribute to endometriosis associated infertility. Despite of this, sperm interaction with the mast cell surface (LAD2) induced a significantly mast cell-degranulation response in the peritoneal fluid from endometriosis which could directly modulate sperm function other than motility. This evidence lead us to suppose that there is, between these elements, an interrelationship which deserves further studies.